Role of professional training of students in ensuring life safety of a person, society, state (Journal of Educational Sciences, 2021)
The purpose of the article is to reveal the role of education, including vocational training, as the main factor in ensuring the safety of life of a person, society and the state in conditions of uncertainty. Ongoing local wars, hybrid conflicts in the world, including an information war associated with a clash of ideologies, reveal many problems, threats and challenges to humanity and further actualize the provision of life safety. In this regard, the life safety of a person, society, state, which is still poorly understood in conditions of uncertainty, may come to the fore in the near future. The modern military-political and socio-economic situation clearly shows that Kazakhstan needs an effective system to ensure the safety of life of a person, society and the state. To achieve the required level of life safety in the current situation, education should become a priority of state policy. This task can be solved by improving the quality of professional training, in particular, the initial military and technological training of students. In the study, a survey of students was conducted to identify interest in military service (1-3 courses). 120 students of professional colleges in Almaty took part in the survey. The survey showed the dynamics of increasing interest in military service and factors negatively affecting the formation of motivation for military service. The authors associate the increase in interest with the study of the course of initial military and technological training of students.Key words: ensuring life safety, intellectual security, education, preparation for military service.